1996
DOI: 10.1007/bf01878133
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of diversity in populations of plant pathogens: the barley powdery mildew pathogen across Europe

Abstract: Understanding population genetics and evolution within species requires recognition of variation within and between populations and the ability to distinguish between the potential causes of an observed distribution of variation. For this aim several established indices of diversity, and a novel one, were applied to population samples of the barley powdery mildew pathogen, Erysiphe graminis f. sp. hordei. Random spore samples were obtained from the air along transects through regions of interest across large p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…cations that concerned the characterization of processes related to pathogenesis or symbiosis: 45 publications for fungusplant pathosystems, 37 for bacterium-plant systems, 14 for rhizosphere systems, 13 for mycorrhizae, and the remainder for soils, foods, and food-processing factories. The objectives of these studies were, for example, to determine the similarity of populations of a given plant pathogen from different origins or the overall diversity within a specific group of a plant pathogen or food spoilage organism (11,16,32,51,62,121,142,152,189,221). We did not consider studies focused solely on molecular phylogenetics or on the diversity of specific alleles within pathogen or symbiont populations.…”
Section: Methods Used For Characterizing Biodiversitymentioning
confidence: 99%
See 1 more Smart Citation
“…cations that concerned the characterization of processes related to pathogenesis or symbiosis: 45 publications for fungusplant pathosystems, 37 for bacterium-plant systems, 14 for rhizosphere systems, 13 for mycorrhizae, and the remainder for soils, foods, and food-processing factories. The objectives of these studies were, for example, to determine the similarity of populations of a given plant pathogen from different origins or the overall diversity within a specific group of a plant pathogen or food spoilage organism (11,16,32,51,62,121,142,152,189,221). We did not consider studies focused solely on molecular phylogenetics or on the diversity of specific alleles within pathogen or symbiont populations.…”
Section: Methods Used For Characterizing Biodiversitymentioning
confidence: 99%
“…Alternatively, the investment in time and labor for multiple tests of hypotheses may have been prohibitive for some studies. For certain studies, such as those addressing changes in population structure or composition over decades (196) or across a wide range of geographic regions (189), multiple independent tests are virtually impossible or very impractical. However, for other types of studies, we could not identify what led to the publication of results of only a single experiment, a single sampling campaign, or a single set of strains.…”
Section: Measuring the Impact Of The Environment Space And Timementioning
confidence: 99%
“…Then, number of isolates in each MCG also was summarized for both species in the three valleys. In addition to the number of MCGs, in-species MCG diversity, including Shannon's H, Simpson, and Berger-Parker indices (15,24), were determined in each valley for both species. The probability that samples from different valleys (two valleys for S. sclerotiorum and three valleys for S. minor) came from the same population was estimated with a bootstrap procedure (PAST, version 1.40) (13).…”
Section: Fieldmentioning
confidence: 99%
“…No surprisingly, VALÉRIO et al (2004) told that the total diversity values showed for all mixtures among different sorghum lineages, with different anthracnose resistance levels, did not supported pathogen populations phenotypically more diverse than that observed in their respective pure stands. Therefore, with rare exceptions (BROWNING & FREY, 1981;MULLER et al, 1996), the diversity degree maintained in a mixture seems to be positively related to the degree of control of disease supplied by a certain mixture (DILEONE & MUNDT, 1994). In a wider aspect, is that mixtures would select for the complex races frequency increase, that is, those with corresponding virulences to the more than a resistance gene in a mixture.…”
Section: Implications and Consequences Of The Use Of Mixturesmentioning
confidence: 99%